PERTANGGUNG JAWABAN PIDANA TERHADAP SOPIR TRUK KARENA KELALAIAN MENGAKIBATKAN ORANG LAIN MENINGGAL DUNIA - Arina Merlita Minanjar (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTFactors causing traffic accidents in Samarinda City first due to human factors, vehicles, and environment / road. The criminal liability to truck drivers resulting from his negligence resulted in the death of another person in Samarinda City under the Criminal Code CHAPTER XII on Reparation and Rehabilitation under Article 95 paragraphs 1 through 5, Article 96 paragraphs 1 through 2, Article 100 paragraphs 1 through 2 and Law no.The stages to avoid traffic accidents in Samarinda City, concentration in driving, if the body is not fit should not be forced to do activities such as driving, do not take anything while driving, do not use the mobile while driving, pay attention to visibility, so as not to cause traffic accidents, stop in a drowsy, be patient in riding, succumb to reckless people, use seatbelts before running a vehicle, red triangle when the vehicle stops on the street and do not park in any place. in terms of vehicles, no bribery and illegal levies, in passing weigh bridges due to overload, so that roads are not damaged due to overload, carrying in accordance with the load so that when driving is not experiencing difficulties such as rolled while carrying loads that exceed the capacity pay attention to the condition of the vehicle such as brake pads are replaced, water radiator is always filled so that the engine is not hot, and the tires used must be good so that the driver and the goods do not experience road obstacles. roads and neighborhoods, be careful with perforated roads, landslides and floods, be careful and not speed with a winding road, stop when the weather is fog or smoky to keep drivers and goods safely carried safely.